2019
DOI: 10.1002/er.5000
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic conversion of ethane: status and perspective

Abstract: Ethane (C 2 H 6 ) is a main component of natural gas and a notable contributor to photochemical pollution and ozone production in the atmosphere. It is important to convert ethane to useful chemicals. The photocatalytic conversion of ethane is promising but challenging. As the first review article in this area, we summarize the recent important progresses in photocatalytic ethane conversion, with an emphasis on (1) homogeneously functionalization and (2) heterogeneously partial oxidation of ethane. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…As was mentioned earlier, one of the promising processes for producing ethylene, is the ODH of ethane in the presence of CO 2 as a soft oxidant [50]. Since ODH with CO 2 takes place at high temperatures, photo-oxidation of ethane with CO 2 can be a possible way to improve the process [93][94][95]. Zhang and co-workers demonstrated that the Pd on TiO 2 materials are prospective catalysts for the photocatalytic ODH with CO 2 at room temperature [94].…”
Section: New Trends In the Ethane Conversion Processmentioning
confidence: 96%
See 1 more Smart Citation
“…As was mentioned earlier, one of the promising processes for producing ethylene, is the ODH of ethane in the presence of CO 2 as a soft oxidant [50]. Since ODH with CO 2 takes place at high temperatures, photo-oxidation of ethane with CO 2 can be a possible way to improve the process [93][94][95]. Zhang and co-workers demonstrated that the Pd on TiO 2 materials are prospective catalysts for the photocatalytic ODH with CO 2 at room temperature [94].…”
Section: New Trends In the Ethane Conversion Processmentioning
confidence: 96%
“…Photocatalysis is an alternative approach using clean solar energy to activate the ethane molecule and CO 2 under mild conditions [93]. As was mentioned earlier, one of the promising processes for producing ethylene, is the ODH of ethane in the presence of CO 2 as a soft oxidant [50].…”
Section: New Trends In the Ethane Conversion Processmentioning
confidence: 99%
“…Meanwhile, Bronkema et al. have also substantiated similar views that nearly 90 % of methanol adsorbed on anatase in the form of surface‐bound Ti−OCH 3 , suggesting that methoxy can be served as a primary hole scavenging trap, thus extending the lifetime of conduction electrons [102–106] …”
Section: Dissociative Adsorption Of Methanol To Methoxymentioning
confidence: 84%
“…However, most of the processes for converting ethane are thermodynamically not feasible at room temperature due to the positive Gibbs energy change except for combustion or partial oxidation with oxygen. 2 Traditionally, ethane conversion has been studied in both homogeneous and heterogeneous catalytic systems. Homogeneous conversion and functionalization of ethane involve harsh reaction conditions such as the use of strong electrophiles, superacids, and strong oxidants and require noble metals such as iridium, rhodium and ruthenium complexes.…”
Section: Introductionmentioning
confidence: 99%